General practitioners' attitudes towards and experiences with referrals due to supplemental health insurance. (2nd May 2017) - Andersen, Merethe K; Pedersen, Line B; Dupont, Michael; Pedersen, Kjeld Møller; Munck, Anders; Nexøe, Jørgen
Abstract: Background: Supplemental health insurances (SHI) cover 38% of the Danish population. SHI can give faster access to, and additional treatment from, private health providers. However, this is contingent on a referral from the general practitioner (GP), further complicating clinical decision-making. Objectives: To describe GPs' attitudes to SHI and their experiences with patients holding SHI. Moreover, we analysed associations between different GP characteristics; e.g. gender, age, practice type, own SHI status and their attitudes to and experiences with SHI. Methods: A questionnaire was mailed to 3321 GPs focusing on three issues: (i) Attitudes towards the public health care system. (ii) Perceptions of the impact of SHI. (iii) Experiences with patients holding SHIs. Results: The response rate was 64%. Overall, GPs found that SHIs contribute to inequality (83%) and overtreatment (90%). However, 46% often feel under pressure to refer SHI patients to specialist care, even though not medically indicated, while 11% always or often refer SHI patients unconditionally. Both groups perceive SHI patients more insistent on getting referrals than patients without SHI. Conclusion: Even though a majority of GPs associate SHI with overtreatment and inequality in health, many GPs feel under pressure to refer patients holding SHI for treatments or examinations that are not medically warranted. Some GPs even refer these patients without further examination or questioning. Insistent SHI patients may partly explain this paradox. Future research should illuminate SHI patients' courses in the private as well as the public healthcare system with regards to medical indications and health outcome measures focusing on inequality and overtreatment.